Variation among Staphylococcus aureus membrane vesicle proteomes affects cytotoxicity of host cells. (April 2016) - Jeon, Hyejin; Oh, Man Hwan; Jun, So Hyun; Kim, Seung Il; Choi, Chi Won; Kwon, Hyo Il; Na, Seok Hyeon; Kim, Yoo Jeong; Nicholas, Asiimwe; Selasi, Gati Noble; Lee, Je Chul
Abstract: Staphylococcus aureus secretes membrane-derived vesicles (MVs), which can deliver virulence factors to host cells and induce cytopathology. However, the cytopathology of host cells induced by MVs derived from different S. aureus strains has not yet been characterized. In the present study, the cytotoxic activity of MVs from different S. aureus isolates on host cells was compared and the proteomes of S. aureus MVs were analyzed. The MVs purified from S. aureus M060 isolated from a patient with staphylococcal scalded skin syndrome showed higher cytotoxic activity toward host cells than that shown by MVs from three other clinical S. aureus isolates. S. aureus M060 MVs induced HEp-2 cell apoptosis in a dose-dependent manner, but the cytotoxic activity of MVs was completely abolished by treatment with proteinase K. In a proteomic analysis, the MVs from three S. aureus isolates not only carry 25 common proteins, but also carry ≥60 strain-specific proteins. All S. aureus MVs contained δ-hemolysin (Hld), γ-hemolysin, leukocidin D, and exfoliative toxin C, but exfoliative toxin A (ETA) was specifically identified in S. aureus M060 MVs. ETA was delivered to HEp-2 cells via S. aureus MVs. Both rETA and rHld induced cytotoxicity in HEp-2 cells. In conclusion, MVs from clinical S. aureus isolates differ with respect to cytotoxic activity in host cells, and these differences may result from differences in the MV proteomes. Further proteogenomic analysis or mutagenesis of specific genes is necessary to identify cytotoxic factors in S. aureus MVs. Highlights: MVs from clinical Staphylococcus aureus isolates have different cytotoxic activity toward host cells. Proteins in S. aureus MVs are directly responsible for the apoptosis of host cells. MVs from different S. aureus isolates carry strain-specific proteins. S. aureus toxins, Hld, Hlg, leukocidin D, ETA, and ETC, are secreted by MVs.